Excel dashboards & reports - Alexander, Michael, 1972-; Walkenbach, John. (Hoboken, NJ : Wiley, 2010)
The go to resource for how to use Excel dashboards and reports to better conceptualize data. Many Excel books do an adequate job of discussing the individual functions and tools that can be used to create an "Excel Report." What they don't offer is the most effective ways to present and report data. Offering a comprehensive review of a wide array of technical and analytical concepts, Excel Reports and Dashboards helps Excel users go from reporting data with simple tables full of dull numbers, to presenting key information through the use of high-impact, meaningful reports and dashboards that work.
pt. 1. Moving from spreadsheets to dashboards -- pt. 2. Excel chart basics -- pt. 3. Going beyond tables and charts -- pt. 4. Creating advanced dashboard components -- pt. 5. Automating your dashboards and reports -- pt. 6. Working with the outside world.
Print version record.
John Wiley and Sons
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Microsoft Excel (Computer file); Dashboards (Management information systems); Statistics -- Charts, diagrams, etc; Business report writing; Balanced scorecard (Management); Business writing; Tableaux de bord (Gestion); Statistique -- Tableaux, graphiques, etc; Style commercial; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Business writing; Balanced scorecard (Management); Business report writing; Dashboards (Management information systems); Statistics; Charts, diagrams, etc; dissertations; Academic theses; 2